CGIAR Research Program on Climate Change, Agriculture and Food Security - Plan of Work and Budget 2021 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
While no substantial changes have been made to the overall balance of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Flagships (FP) nor to its Theory of Change, the introduction of Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) to the program is an exciting development for CCAFS Flagships 1, 2, and 4, as well as for the teams in East Africa (EA) and West Africa (WA).